Best black troops in the world : British perceptions and the making of the Sepoy, 1746-1805 - Wickremesekera, Channa (New Delhi : Manohar, 2002)
British perceptions on the Indian soldiers in the formation of the East India Company's army
Includes bibliographical references and index
Keywords: India -- History, Military; India -- Armed Forces -- History